Scheme of allegation and proof of Foreign Law and Lex Loci Delicti Commissi. Comment on the judgment of the Spanish Court of Appeal of the Balearic Islands of 13 December 2018 - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The foreign Law must be alleged and proven as to its existence, validity and content, allowing the Court to use the means of inquiry it deems necessary for its application. It is the party that invokes it to whom it corresponds to demonstrate the content and its validity. This is seen in the Judgment of the Spanish Court of Appeal of the Balearic Islands of 13 December 2018, where the presents two reports on foreign law; the Court rejects both reports noting that they do not see any specialty of foreign law on the ownership of the property; Regarding the report on passive legitimation under the law of Curaçao and the Netherlands, it was unnecessary in the case of a non-contractual obligation, so under the Lex Loci Delicti Commissi the Spanish Law will apply, since the damage occurred in the national territory.